Metacommunicative Comments in the Internet Dialogue: Possible Grounds for Classification - Bobko, Tatyana (Respectus Philologicus, 2015)
This article discusses three reasons for the typology of metacommunicative statements: the object of statements (the referent and reflexivity / non-reflexivity of the statements), a way of expressing metacommunicative intentions, and the pragmatic orientation of the statements, the article as well discusses the problems of classification, in particular, the difficulties of distinguishing metatext and metacommunicative comments. The analysis is performed on the basis of the popular Belarusian Internet resources. Three reasons for the typology of metacommunicative statements give the opportunity to construct their model, systematizing all the variety of real metacommunicative statements. Modelling structural and substantial characteristics of metacommunicative statements allows to identify those aspects of communication that are important or, on the contrary, unimportant in the eyes of a speaker, as well as the preferences of native speakers in the expression of metacommunicative intentions.